EULER AND EXPONENTIAL ALGORITHM IN VISCOELASTIC ANALYSES OF LAMINATED GLASS - Jaroslav Schmidt; Alena Zemanová (Acta Polytechnica CTU Proceedings)
Laminated glass combines two remarkable materials: glass and a polymer ply. While glass is stiff and brittle, the polymer ply is a rate-dependent compliant material. Together, they form a material which keeps the aesthetic value of glass, and due to the polymer, no fragile collapse appears. The polymer ply exhibits time- and temperature-dependency, whereas glass suffers from brittle fracture, which makes the analysis difficult. In this article, a 2D sectional plane-stress model for the viscoelastic analysis of laminated glass is presented. This study presents one step in the development of a phase-field-based damage solver for laminated glass to select the optimal time-integration scheme for a quasistatic-analysis and later also for dynamics. The validation against experimental data is provided, and the model reduction is also discussed.